DEVELOPING ICT-BASED TEACHING MATERIALS OF ENGLISH FOR MATHEMATICS COURSE - PUJI ASTUTI; YUSUF HARTONO (Sriwijaya University Learning and Education International Conference, 2016)
The information and communication technology (ICT) has been used as amedium of learning. The conventional method is still monotonous and rigid.Therefore, students and lecturer can take advantage of e-learning in the learningprocess. Hence, this study in the course of English for Mathematics aims todevelop teaching materials with an integration of ICT: online discussions,learning videos, access to online materials, and online quiz. The findings showthat the instructional videos that were developed by lecturers were easy to deliverto the students by this e-learning process. The students might watch the videobefore the class then discuss and share the new knowledge in discussion forum.Furthermore, this ICT based learning facilitated the lecturers to assess students’online activities: like forum discussions, exercises, and developed quiz withoutbeing limited by space and time.